2007
DOI: 10.1017/s0022215107007906
|View full text |Cite
|
Sign up to set email alerts
|

Patient mobile telephone ‘text’ reminder: a novel way to reduce non-attendance at the ENT out-patient clinic

Abstract: Sending text message reminders is a simple and cost-effective way to improve non-attendance at ENT out-patient clinics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 10 publications
2
94
1
Order By: Relevance
“…57,72,79 There are few figures to show the failure rates of sending SMS reminders to patients. In an Irish audit of non-attendance rate at ear, nose and throat outpatients clinics following the introduction of a text reminder system, Geraghty et al 94 reported that only 2-3% of people failed to receive their text message reminder as a result of incorrect data entry. Similarly, in an Australian study 95 to evaluate the operational and financial efficacy of sending SMS text message reminders to the mobile telephones of parents of young children with scheduled outpatient clinic appointments, only 0.4% of recipients contacted the outpatient services stating that they had no knowledge of the scheduled appointment.…”
Section: Short Message Service Remindersmentioning
confidence: 99%
See 1 more Smart Citation
“…57,72,79 There are few figures to show the failure rates of sending SMS reminders to patients. In an Irish audit of non-attendance rate at ear, nose and throat outpatients clinics following the introduction of a text reminder system, Geraghty et al 94 reported that only 2-3% of people failed to receive their text message reminder as a result of incorrect data entry. Similarly, in an Australian study 95 to evaluate the operational and financial efficacy of sending SMS text message reminders to the mobile telephones of parents of young children with scheduled outpatient clinic appointments, only 0.4% of recipients contacted the outpatient services stating that they had no knowledge of the scheduled appointment.…”
Section: Short Message Service Remindersmentioning
confidence: 99%
“…as paediatric. In six papers 94,95,98,106,108,109 in this systematic review, 44 the SMS reminders targeted patients attending paediatrics clinics. In paediatric settings, the SMS reminder was sent to the young patient or their parent/ carer; in the non-randomised study by Stott and Gray, 109 SMS reminders were sent directly to the young people.…”
Section: Proposition F: Distal/proxy Individual Attributesmentioning
confidence: 99%
“…Liu et al (18) reported that telephone-based re-education the day before colonoscopy improved the quality of bowel preparation and the polyp detection rate. Several previous studies found that telephone and SMS reminders were associated with an improvement in outpatient attendance (19)(20)(21)(22)(23). Therefore, in patients with prolonged waiting times to colonoscopy, reminders may also be helpful for improving the quality of bowel preparation.…”
Section: Discussionmentioning
confidence: 98%
“…Providers using health IT to connect with their patients may improve overall patient-provider communication and also help to promote patient autonomy and empower patients' with management of their own health. Providers using health IT tools to communicate with patients have reported improved medication adherence and appointment compliance for various ailments (4,(23)(24)(25)(26). Whether health IT applications are preferred by patients and whether a broader disease population can effectively use and benefit from such devices remain unclear.…”
Section: Discussionmentioning
confidence: 99%